ETHNOLINGUISTIC MARKERS IN POLITICAL DISCOURSE: IDENTITY CONSTRUCTION AND LEGITIMIZATION IN UZBEK AND ENGLISH TEXTS - Isokova Feruza Shamsiddin kizi (Modern American Journals, 2025)
This article analyzes how ethnolinguistic markers function as persuasive resources in Uzbek and English political discourse, focusing on identity construction and legitimation. Using a matched corpus of public political texts, it combines corpus-assisted keyword/concordance analysis with segment-level qualitative coding. Ethnolinguistic markers (e.g., people–nation labels, cultural value keywords, historical anchors, phraseology, and metaphors) are mapped to identity functions and interpreted through van Leeuwen’s legitimation categories. The study proposes a replicable coding model and shows how culture-indexing language strengthens “why this must be done” justification in political texts.
Keywords: Ethnolinguistic markers; political discourse; Uzbek; English; identity construction; legitimation; corpus-assisted discourse analysis; van Leeuwen framework; cultural keywords; metaphor